Design and verification of a single roll rapid solidification injection nozzle for Mg-Al-Ca anode material for magnesium rechargeable batteries using by CAE - KIRIMOTO, Yuichi; TSUKEDA, Tadayoshi; AIDA, Tetsuo; NEMOTO, Yasunori; TABATA, Hironobu; HAGA, Toshio; KURIHARA, Hideki; SUZUKI, Mayumi (Keikinzoku, 2024)
In the development of anode materials for magnesium rechargeable batteries, our research team has discovered the potential of the single roll rapid solidification method as a manufacturing method. The requirements for the fabrication of anode materials by the single roll rapid solidification method are thinness, length, width, and a ribbon with good surface properties. Therefore, in this study, the behavior of the molten metal inside the nozzle was confirmed using general-purpose thermal-fluid CAE software. The nozzle interior and nozzle aperture geometry are designed considering the results. The models considered in the CAE analysis are the slope angle of the nozzle interior, the length, area, and shape of the opening gate. The nozzle model with good results in the CAE analysis was fabricated, and ribbons were fabricated by the same method. The appearance of the produced ribbons was very good, and the luster peculiar to the metal was confirmed. It was found that ribbon thickness of less than 100 μm could be produced under the condition of 25 m/s peripheral speed. Investigation of hole defects on the surface confirmed that the defect rate decreases as the thickness of the ribbon increases.